STRAWBERRY RESPONSE ON LIQUID INORGANIC NUTRITION AND ORGANIC LIQUID FERTILIZER IN AGGREGATE CULTURE - Sri Rahayu; Rini Susana; Siti Hadijah (Jurnal Sains Pertanian Equator, 2019)
This study aimed to get the best combination of inorganic nutrients and organic liquid fertilizer of coconut fiber as a nutrient solution for aggregate culture on growth and yield of strawberries. The study was conducted at from February 14th to April 25th 2019. This study used a Completely Randomized Design (CRD). The treatment given as combination of inorganic nutrients and organic liquid fertilizer was five levels of: k0 (100% organic liquid fertilizer), k1 (75% inorganic nutrients), k2 (75% inorganic nutrients with organic liquid fertilizer TDS 1.300 ppm), k3 (75% inorganic nutrients with organic liquid fertilizer TDS 1.800 ppm), and k4(100% inorganic nutrients). Variables observed such as root volume, plant height, leaf number, number of stolons, number of flowers, number of fruits, fruit and dry weight of strawberry plants. The results showed that application a combination of imorganic nutrients and organic liquid fertilizer did not increased the growth and yield of strawberries. Providing 75% of inorganic nutrition increased the growth and yield the same as given 100% of inorganic nutrition. Keywords: inorganic nutrition, organic liquid fertilizer, strawberries.